Електромагнітна сумісність складноструктурованих електропостачальних систем промислових підприємств - Бедерак, Ярослав Семенович (НТУ "ХПІ", 2014)
Проведено дослідження режиму роботи електропостачальної системи промислового підприємства з здвоєним струмообмежувальним реактором 10 (6) кВ, до однієї вітки якого підключена конденсаторна установка, а до другої – асинхронні електродвигуни, при наявності в системі джерела вищих гармонік. Запропоновані заходи з забезпеченння електромагнітної сумісності в таких мережах у різноманітних випадках підключення джерела вищих гармонік до мережі.

The publication is devoted to research mode of power supply systems of industrial enterprises in which a dual current limiting reactor is installed. To the first branch is connected a capacitor installation, and induction motors is connected tothe second one. Connection of the source of higher harmonics to the reactor branch with induction motors or to the external circuit can cause resonance of currents or voltages. The calculation sequence of the resonance frequency in both cases of connections of higher harmonics source was determined.
Electromagnetic compatibility of structure complex systems of power supply on industrial enterprises
Keywords: конденсаторна установка; здвоєний струмообмежувальний реактор; вищі гармоніки; резонанс; capacitor installation; dual current-limiting reactor; harmonics; resonance; electromagnetic compatibility